Pesher and hypomnema: a comparison of two commentary collections from the Hellenistic-Roman period - Hartog, Pieter B. (Studies on the texts of the desert of Judah, 2017)
Introduction -- The Hypomnemata and the Pesharim as Expressions of Intellectual Culture -- Textual Scholarship and the Physicality of the Hypomnemata -- Textual Scholarship and the Physicality of the Pesharim -- A Bifold Structure -- Structure and Scholarship in the Hypomnemata -- Structure and Interpretation in the Pesharim -- Describing Hermeneutics -- A Hermeneutical Profile of the Hypomnemata -- A Hermeneutical Profile of the Pesharim -- Pesher and Hypomnema.